2021
DOI: 10.1088/1755-1315/670/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Microbiological Stability of Quinoa-enriched Wheat Bread

Abstract: Quinoa flour has high nutritional qualities and is a promising source of functional food ingredients for baked goods. Quinoa was successfully used for enriching wheat bread by domestic and foreign researchers. However, increasing the concentration of quinoa flour decreases the volume yield of wheat bread. This study ultimately aims to increase the organoleptic and structural indexes and the microbiological stability of bread enriched by 17% quinoa flour and 2% wheat protein isolate. We compared the qualities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A texture profile analysis (TPA) model was performed with a penetration distance of 4 mm using a cylindrical probe (15 mm diameter, 20 mm height). The speed of the probe was one mm/s with a trigger of 7 g. The analyzer was connected to a computer that documented data via a software program [21,22]. The firmness of the yogurt samples was estimated and defined as the force necessary to attain a given deformation or the force necessary to reach the maximum depth.…”
Section: Firmness Of Yogurtmentioning
confidence: 99%
“…A texture profile analysis (TPA) model was performed with a penetration distance of 4 mm using a cylindrical probe (15 mm diameter, 20 mm height). The speed of the probe was one mm/s with a trigger of 7 g. The analyzer was connected to a computer that documented data via a software program [21,22]. The firmness of the yogurt samples was estimated and defined as the force necessary to attain a given deformation or the force necessary to reach the maximum depth.…”
Section: Firmness Of Yogurtmentioning
confidence: 99%
“…When the added sourdough had a pH of between 3.5 and 4, just 15% of sourdough was needed to prevent visible rope formation [93]. Interestingly, breads prepared with the same amounts of lactic acid as the dough containing 20% sourdough did not prevent Bacillus growth and subsequent rope development, suggesting that rope formation is prevented by the combination of reduced pH and low-molecular-mass compounds produced by LAB [94,95]. Mantzourani et al [70] studied sourdough breads prepared with kefir grains, which showed good results against rope spoilage by Bacillus spp.…”
Section: Prevention Of Rope Formation In Breadmentioning
confidence: 99%
“…Additionally, 2% of dry gluten was added to the composition of the recipe, and a complex ferment of lactic acid bacteria (LAB) was introduced, which made it possible to increase the quantity and quality of gluten. When comparing different technologies for preparing dough, the advantage was given to the use of a steam-free method with LAB, which made it possible to improve the structural and mechanical characteristics of the dough, reduce the duration of fermentation in comparison with the traditional method and increase the dimensional stability, porosity, volumetric bread yield and organoleptic characteristics [18]. The design of the optimal bread recipe based on the obtained experimental results was carried out using the developed computer program.…”
Section: Introductionmentioning
confidence: 99%